Accusers of capitalism: masculinity and populism on the Scottish radical left in the late twentieth century. (2nd April 2020) - Gibbs, Ewan; Scothorne, Rory
ABSTRACT: Scotland offers a valuable case study of the ways in which a combination of transnational and national structural changes can open up national articulations of 'hegemonic masculinity' to subaltern contestation. During the late twentieth century, the subjection of an imagined industrial community to both global capital flows and state planning priorities produced opportunities for the re-articulation of hegemonic masculinity as a means of securing subaltern agency within a counter-movement against neoliberalism. The defiant but respectable left-wing 'hard man' – a signifier of collective morality and populist counter-legitimacy against state and market – was mobilized by leaders espousing an often explicitly gendered vision of respectable militancy. This article identifies three such leaders: Jimmy Reid, Jim Sillars and Tommy Sheridan. Each leader advocated resistance to market forces and the state by personally embodying a traditional masculine authority rooted in the cultural imaginary of industrial working-class communities. This article examines the parameters of Scottish left-wing populism before analysing its decline in the late twentieth century. Under devolution this populism has been displaced by a more inclusive 'civic' nationalism less comfortable with gendered and militant rhetoric, as the social basis of masculine left populism has been eroded.